The Contribution of Serum Complement Component 3 Levels to 90-Day Mortality in Living Donor Liver Transplantation - Fukui, Saeko; Hidaka, Masaaki; Fukui, Shoichi; Morimoto, Shimpei; Hara, Takanobu; Soyama, Akihiko; Adachi, Tomohiko; Matsushima, Hajime; Tanaka, Takayuki; Fuchigami, Mai; Hasegawa, Hiroo; Yanagihara, Katsunori; et al. (Frontiers in Immunology, 2021)
We conducted this research to investigate the contribution of the complement system in liver transplantation because there has been insufficient clinical research on this matter although that has been elucidated in the process of solid organ transplantation, including kidney transplantation. This research provides both fundamental but unestablished information about the dynamics of the complement components after liver transplantation and clinical information, such as the prognostic value of complements for predicting survival. Specifically, while C3 and C4 increase in a time-dependent manner after living donor liver transplantation (LDLT), low levels of serum C3 at 2 weeks after LDLT may distinguish subsequent mortality. Furthermore, we observed some interesting relationships between the complement components and the peripheral lymphocyte subpopulation. Our results can contribute to a basis for monitoring of complement component levels after LDLT. Careful investigations of hypocomplementemia may reduce the mortality rate, which also suggests the complement contributions in fields of organ injury and regeneration. At the same time, drugs targeting the complement system have been used in clinical trials and have shown efficacy in kidney transplantation, and more medications will be available in the near future. The present research will offer essential information when are considered for use in liver transplantation.